Effect of accounting profit, cash flow, and return on assets on stock returns (Empirical Study on Consumer Goods Industry Listed on the Indonesia Stock Exchange Period 2007 -2009) - sidik sidik (IHSA Institute, 2023)
The goal to be achieved in this study is to determine the effect of accounting profit, cash flow components, return on assets on stock returns. The research data was obtained from the official website of the Indonesia Stock Exchange. The object of this research is all consumer goods industry companies listed on the Indonesia Stock Exchange for the period 2007-2009. Determination of the sample in this study using a purposive sampling method based on the availability of data during the study period and the type of data is secondary, while the analytical method used is a multiple linear regression model. The results of this study show that accounting profit, operating cash flow, investment cash flow, funding cash flow, and return on assets together have a significant influence on stock returns. While partially the effect is different, accounting profit, investment cash flow and funding cash flow each have a significant negative effect on stock returns. Operating cash flow has no significant positive effect on stock returns and ROA has a significant positive effect on stock returns. The conclusion of this study shows that the regression model formed with independent variables consisting of accounting profit, operating cash flow, investment cash flow, financing cash flow and return on assets can be used to predict stock returns in the consumer goods industry.